One-dimensional singular problems involving the p-Laplacian and nonlinearities indefinite in sign - Kaufmann, Uriel (2016)
Fil: Kaufmann, Uriel. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía, Física y Computación; Argentina.